Incidence and Risk Factors of Anterior Arch Fracture of the Atlas Following C1 Laminectomy Without Fusion. Issue 10 (15th May 2018) - Shimizu, Takayoshi; Otsuki, Bungo; Fujibayashi, Shunsuke; Kumamoto, Shinji; Hijikata, Yasukazu; Shimizu, Yu; Takemoto, Mitsuru; Ota, Masato; Ito, Hideo; Matsuda, Shuichi
Abstract : Study Design: A retrospective multicenter study. Objective: To identify the incidence of anterior arch fracture (AAF) of the atlas following C1 (first cervical vertebra) laminectomy without fusion, and its risk factors. Summary of Background Data: C1 laminectomy without fusion is a widely accepted surgical procedure performed to decompress the spinal cord that is compromised at the C1/C2 level, but without instability. Several case series have reported spontaneous AAF following this procedure. However, the incidence of post-laminectomy AAF and its risk factors have not been studied. Methods: This retrospective study included patients who underwent C1 laminectomy without fusion in any of the four participating institutions between April 2002 and March 2016. The incidence of AAF following C1 laminectomy was determined, and the included patients were grouped into those who developed AAF (AAF group) and those who did not (non-AAF group). Patient demographics and radiographic parameters including subaxial cervical balance on x-ray (C2–7 sagittal vertical axis, C2–7 lordosis, C2–7 coronal cobb angle, and T1-slope), and morphology of the atlas on computed tomography (CT) scan were compared with the AAF and non-AAF groups. Results: Seventy patients who underwent C1 laminectomy without fusion were included in the study. The incidence of AAF was 14.2% (10/70). Multivariate analysis revealed that a large inferior facet angle (IFA, defined as the coronal inclination angle of the C1/2 facet as measured on CT) and the presence of subaxial ankylosis (bony ankylosis below C2 on CT) were independent risk factors for AAF. There were no significant differences in the subaxial cervical balance as measured on x-ray between the AAF and non-AAF groups ( P > 0.05). Conclusion: The incidence of AAF after C1 laminectomy without fusion is not uncommon. Preoperative assessment using CT may identify patients at high risk of AAF. Level of Evidence: 4